2022
DOI: 10.21037/cdt-21-577
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of surgical repair of anterior or posterior ventricular septal rupture after myocardial infarction

Abstract: Background: Ventricular septal rupture (VSR) is a rare and fatal complication of myocardial infarction.Surgery is the main treatment for the condition. It is currently believed that surgery is less effective for posterior VSR than for anterior VSR. The objective of this study was to investigate the clinical outcomes of surgical treatment for myocardial infarction combined with an anterior or posterior VSR.Methods: This was a single-center, retrospective, observational, cohort study. Clinical data of 68 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…However, in another study which enrolled 148881 aged patients (67-71 years) with first-onset STEMI, all were divided into the CR group (n=408, with free wall rupture) and the control group (n=148473, without CR). They found that the occurrence of DM history was significantly lower than that in the control group (18% vs. 24%), and DM was a protective factor of ventricular free wall rupture (OR=0.67,95%CI: 0.52-0.87) (14). Meanwhile, for patients with papillary muscle rupture or ventricular septum perforation, diabetes is more rare (15,16), and several published studies did not detect the association between DM and the risk of papillary muscle rupture or ventricular septum perforation (P>0.05).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, in another study which enrolled 148881 aged patients (67-71 years) with first-onset STEMI, all were divided into the CR group (n=408, with free wall rupture) and the control group (n=148473, without CR). They found that the occurrence of DM history was significantly lower than that in the control group (18% vs. 24%), and DM was a protective factor of ventricular free wall rupture (OR=0.67,95%CI: 0.52-0.87) (14). Meanwhile, for patients with papillary muscle rupture or ventricular septum perforation, diabetes is more rare (15,16), and several published studies did not detect the association between DM and the risk of papillary muscle rupture or ventricular septum perforation (P>0.05).…”
Section: Discussionmentioning
confidence: 96%
“…Based on the analysis of 6712 STEMI patients in our research center, we found the neutrophil count ≥ 9 × 10 9 /L was an independent risk factor for ventricular free wall rupture, but DM was not an risk factor for CR. Diabetes is a common complication among elderly STEMI patients, which will significantly increase the risk of adverse cardiovascular events (14). Recently, we retrospectively analyzed a total of 10284 patients with STEMI admitted to Beijing Anzhen Hospital from January 2012 to March 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Although several surgical interventions have been developed, mortality and complications associated with surgical management are still high, especially in terms of transventricular approaches. [2] Among these patients, anterior VSR (66%-78%) and posterior VSR accounted for about 17%-22%. [3] Compared with surgical repair of anterior VSR, the operative mortality of posterior VSR is higher.…”
mentioning
confidence: 94%
“…[5] Exclusion of infarction by left ventriculotomy is an additional injury to already unstable myocardium. [2] There are several problems in ventriculotomy: (1) remodeling after MI and making a large incision on the free wall of the ventricle can affect postoperative low cardiac function and ventricular arrhythmia; and (2) larger sutures and tight closure of the ventricles also reduce the remaining ventricular volume and worsen the diastolic function of the heart. [6] Also, there was a technical obstacle of difficult dissection with uneasy access to the previous left ventriculotomy in this case, which was complicated by a patent coronary artery bypass graft.…”
mentioning
confidence: 99%